Care and Humor in Contemporary Indigenous Literature: Personal Readings - Kuligowski, Waldemar (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
Today, literature written by women and men from Indigenous communities from the United States and Canada cannot be limited to collections of nostalgic poetry, anthologies of sublime speeches or picturesque selections of myths and legends. This literature touches on almost all topics typical of contemporary word art, undoubtedly belonging to the “world republic of literature”. The thesis of the article is that two clear themes for this literature can be identified, which are also important for external recipients. These are: a deeply felt concern for the environment and a particular sense of humor. This thesis has been illustrated with examples of prose and poetry by Natalie Diaz, Inés Hernández-Ávila, Thomas King, Tomson Highway, and Adam Fortunate Eagle. Their works go beyond the patterns present in standard realistic prose, beyond the preferences of the publishing industry, presenting a different, “organic” view of the world.